Coordinated Control of Flywheel and Battery Energy Storage Systems for Frequency Regulation in Diesel Generator-Based Microgrid - Mahdi Faraji; Mohammad Saeed Mahdavi; Venera Nurmanova; Gevork B. Gharehpetian; Mehdi Bagheri (IEEE Access)
Due to the inherent slow response time of diesel generators within an islanded microgrid (MG), their frequency and voltage control systems often struggle to effectively manage rapid load changes. To mitigate this challenge, energy storage systems (ESSs) emerge as pivotal solutions. Flywheel energy storage systems (FESSs) are well-suited for handling sudden power fluctuations because they can quickly deliver or absorb large amounts of electricity. On the other hand, battery energy storage systems (BESSs) excel at storing large amounts of energy for extended periods and can handle gradual changes in power demand. This research introduces a coordinated control mechanism for a mixed energy storage setup that combines BESS and FESS elements to manage the frequency of a standalone MG. A new frequency detection method is employed to assign high, medium, and low-frequency deviations in power distribution to FESS, BESS, and diesel generators, respectively. Simulations are carried out to determine the exact performance of the proposed control method. The MATLAB/Simulink software platform is used to run these simulations. Furthermore, dynamic load changes are precisely emulated using a programmable load emulator enhancing the reliability and relevance of our analysis.